THE MANY FACES OF THE “FOSTER CARE YOUTH” LABEL: HOW YOUNG WOMEN MANAGE THE STIGMA OF OUT-OF-HOME PLACEMENT - Turcotte, Mathilde; Lanctôt, Nadine (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
A number of studies have found that adolescents in foster care expect and perceive stigma related to their “foster care youth” status. Yet, little is known about how this perceived stigma manifests, as well as how youth manage it. The current study therefore aimed to explore how young women with a history in foster care integrate these experiences into their life stories. The focus is on discursive manifestations of stigma in participants’ narratives about placement in foster care, their own perceptions of care-experienced girls and women, as well as how they self-present. Special attention is also given to the ways in which youth try to reduce, deflect, or eliminate stigma. The present study draws on semi-structured interviews conducted with a sample of 20 young women with a history in foster care. Our findings suggest that participants do anticipate and perceive public stigma in relation to their history in foster care. The results also highlight the various strategies used by participants to resist self-stigmatization. The main strategy used was to distance themselves from their “foster care youth” status, insisting that they should never have been placed in foster care and that they are not faring badly as adults, unlike typical care-experienced youth.